KAWIN BEDA AGAMA DAN PERLINDUNGAN HAM : STUDI KRITIS ATAS UNDANG-UNDANG PERNIKAHAN NOMOR 1 TAHUN 1974 DAN UNDANG-UNDANG DASAR 1945 - Yedi Purwanto (Asy-Syari'ah, 2015)
The polemic of Marriage Law Number 1 of 1974 is back into hot issue to be discussed. It reminds to the public discussion in a long history and the dynamics of the appearance of this laws. This time, the spotlight is article 2, paragraph 1 of the Marriage Law Number 1 of 1974 which contains "Marriage is legitimate, if it is done according to the laws of each religion and the belief it". Against with the decision, any parties asked a judicial review to the Constitutional Court (MK) for the article. This paper wants to give exposure of reactions of the people who are doing legal efforts with the proposal, as well as how to find the best solution for its completion. The core problem in this paper is to be appointed about whether or not may interfaith marriage. Referring to the Marriage Law Number 1 of 1974 and the 1945 Constitution, this paper will describe how the views of classical scholars, ulama (Muslim jurists), community leaders, officials and legal experts in the country explain about marriage in different religion.